PENGARUH ECONOMIC VALUE ADDED (EVA), NET PROFIT MARGIN (NPM), RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM (Studi Kasus Perusahaan Properti dan Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2013-2016 - Zaidatul Fadinah; Muhammad Agus Salim; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this research is to determine the effect of economic value added, net profit margin, return on asset, return on equity, earning per share, and price earning ratio to the stock price in property and real estate sector in BEI. Sampling determination technique in this research use purposive sampling, the final sample is 26 companies listed in Indonesia Stock Exchange on 2013-2016. this research take secondary data through the financial statements of each company in Indonesia Stock Exchange website. This study uses multiple linear regression analysis with the help of SPSS 20 for windows. The result of the research shows that EVA has a positive and significant effect on stock price, NPM does not affect the stock price ROA has a negative and significant effect on stock price ROE has no significant effect on stock price EPS has a positive and significant effect on stock prices PER has a positive and significant effect on stock price. Keywords: economic value added, net profit margin, return on asset, return on equity, earning per share, price earning ratio, and stock price.